Neck Pain: Do We Know Enough About the Sensorimotor Control System? - Qu, Ning; Tian, HaoChun; De Martino, Enrico; Zhang, Bin (Frontiers in Computational Neuroscience, 2022)
Neck pain is a worldwide health problem. Clarifying the etiology and providing effective interventions are challenging for the multifactorial nature of neck pain. As an essential component of cervical spine function, the sensorimotor control system has been extensively studied in both healthy and pathological conditions. Proprioceptive signals generated from cervical structures are crucial to normal cervical functions, and abnormal proprioception caused by neck pain leads to alterations in neural plasticity, cervical muscle recruitment and cervical kinematics. The long-term sensorimotor disturbance and maladaptive neural plasticity are supposed to contribute to the recurrence and chronicity of neck pain. Therefore, multiple clinical evaluations and treatments aiming at restoring the sensorimotor control system and neural plasticity have been proposed. This paper provides a short review on neck pain from perspectives of proprioception, sensorimotor control system, neural plasticity and potential interventions. Future research may need to clarify the molecular mechanism underlying proprioception and pain. The existing assessment methods of cervical proprioceptive impairment and corresponding treatments may need to be systematically reevaluated and standardized. Additionally, new precise motor parameters reflecting sensorimotor deficit and more effective interventions targeting the sensorimotor control system or neural plasticity are encouraged to be proposed.